Development of natural-based cosmetic cream containing caffeine for the improvement of appearance of cellulite and slimmimg effect - Nor Hakimah Mohamad (Kulliyyah of Pharmacy, International Islamic University Malaysia, 2019)
Cellulite or lipodystrophy is the result of changes in the subcutaneous adipose tissue which appears irregular and dimply on the surface of skin. This is a major aesthetical concern among women who want to look beautiful. Caffeine has the ability to work as an anti-cellulite as it can stimulate the lymphatic system, vascular flow, and lipolysis of adipose tissue. Mostly commercial caffeine cream products that available in the market contain chemical-based ingredient which might poses side effect to customer and this increase the concern among consumer towards natural product. In addition, this study provided preclinical testing data through in vivo evaluation. This research aimed to develop a natural-based cosmetic slimming and anti-cellulite cream formulation containing caffeine, to characterise the developed cream containing caffeine, and to evaluate the effectiveness of the developed cream containing caffeine as a slimming and anti-cellulite product on human volunteers. First, the concentration of caffeine in the formulation was determined using solubility test and the formulation of oil-in-water cream was prepared from mixing and homogenising three parts of ingredients, which were water-based ingredient, oil components, and additional ingredients. Then, the prepared cream was characterised in terms of physical analysis and phase separation, pH, droplet size, zeta potential, rheological property, and microbial test as well as caffeine content by using HPLC. The base cream and cream containing caffeine then were further subjected to stability study at different storage conditions of 40 ± 2 ℃ with 75% ± 5% relative humidity and 30 ± 2 ℃ with 75% ± 5% relative humidity for 12 weeks. During storage, both creams were evaluated for physical properties (appearance, uniformity, and odour), phase separation by centrifugation, pH, rheological property, zeta potential, droplet size, and microbiological tests in different time intervals at day 0, week 2, week 4, week 8, and week 12. For further study, placebo and caffeine cream containing 2.5% caffeine were prepared and applied to the upper arm and abdomen of 24 healthy volunteers, twice daily in to determine the efficacy of the formulation as an anti-cellulite and slimming agent for 12 weeks. The hydration, elasticity, trans-epidermal water loss, fat thickness, and circumference measurement of abdomen and upper arm of volunteers were evaluated and monitored at baseline (before application of cream), 2nd, 4th, 8th, and 12th week of study to measure the effect produced by the creams. The natural-based cream containing 2.5% caffeine yielded a good organoleptic physical property with no microbial growth and exhibited non-Newtonian fluid behaviour. Besides, the caffeine content, zeta potential, pH value, and droplet size with span of the developed cream were within the acceptable range for emulsion. The prepared cream containing 2.5% caffeine was stable chemically and physically over the period of study with low degradation of caffeine in the cream. The cream containing caffeine was able to improve the appearance of cellulite and gave slimming effect by reducing circumference measurement, fat thickness, and TEWL as well increasing hydration of skin. As a result, a stable and natural-based cosmetic cream containing caffeine for the improvement of cellulite and slimming effect was successfully developed.